1997
DOI: 10.1159/000264440
|View full text |Cite
|
Sign up to set email alerts
|

The Early Amniocentesis Study: A Randomized Clinical Trial of Early Amniocentesis and Midtrimester Amniocentesis

Abstract: The present study provides detailed neonatal and congenital malformation follow-up from 695 women enrolled in a prospective randomized multicenter study comparing the safety and accuracy of early (11–12 weeks of gestation) and midtrimester amniocentesis (15–16 weeks of gestation). No differences were found for total pregnancy loss (difference 0.4%; CI ––3.6 to 4.4%), obstetrical or neonatal outcome. The incidence of congenital anomalies was 2.4 and 2.6% for the early amniocentesis and midtrimester amniocentesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…We calculated that a sample size of 9631 women in each group would be required to demonstrate a reduction in rate of foetal loss from 0.2% among controls to 0.015% in the antibiotic group (power = 90%, alpha = 0.05 two-sided). The latter percentage was derived by an arbitrary estimate of a rate of foetal loss with antibiotic prophylaxis (Johnson et al, 1996;Wilson et al, 1997; The Canadian Early and Mid-trimester Amniocentesis Trial (CEMAT) Group, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated that a sample size of 9631 women in each group would be required to demonstrate a reduction in rate of foetal loss from 0.2% among controls to 0.015% in the antibiotic group (power = 90%, alpha = 0.05 two-sided). The latter percentage was derived by an arbitrary estimate of a rate of foetal loss with antibiotic prophylaxis (Johnson et al, 1996;Wilson et al, 1997; The Canadian Early and Mid-trimester Amniocentesis Trial (CEMAT) Group, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, azithromycin has a long estimated half-life (Ramsey et al, 2003), good tolerability, and few side effects (Johnson et al, 1996;Wilson et al, 1997). However, it is possible that the incidence of azithromycinrelated side effects was over-estimated because questions about side effects were limited to the azithromycintreated group (women in the control group were not asked about specific symptoms).…”
Section: Discussionmentioning
confidence: 99%
“…The safety and diagnostic reliability of early (< 14 + 0 weeks) vs midtrimester (> 15 + 0 weeks) amniocentesis was studied in RCTs in the 1990s. Although a smaller trial ( n = 695) indicated similar rates for total pregnancy loss (7.8% vs 7.4%) and fetal congenital defects (2.4% vs 2.6%), a much larger multicenter RCT ( n = 4374) showed that early (11 + 0 to 12 + 6 weeks) amniocentesis was associated with a significantly higher rate of total fetal losses (7.6% vs 5.9%), fetal talipes (1.3% vs 0.1%) and post‐procedure amniotic fluid leakage (3.5% vs 1.7%), compared with midtrimester (15 + 0 to 16 + 6 weeks) amniocentesis. This may be due to the presence of the extraembryonic celom in the first trimester or the reduced amount of amniotic fluid in the amniotic cavity.…”
Section: Amniocentesismentioning
confidence: 98%
“…The risk of amniotic fluid leakage following amniocentesis is increased up to 24 weeks of gestation. Its occurrence is reported to vary between 1 and 2%. However, in women with amniotic fluid leakage after amniocentesis, spontaneous sealing of the membranes is commonly observed and, compared with cases of spontaneous rupture of membranes at the same gestational age, the risk of perinatal loss is substantially lower ( EVIDENCE LEVEL: 2++ ).…”
Section: Amniocentesismentioning
confidence: 99%
“…Amniocentesis is usually offered to women over 35 years of age, as the risk for conceiving a fetus with Down syndrome starts to increase at this time. The procedure carries an increase in miscarriage rate of about 0.5% [12][13][14]. The analysis of fetal cells from amniotic fluid 54 Fetal Diagn Ther 1998; 13:53-61 Crang-Svalenius/Dykes/Jörgensen takes 2-3 weeks to complete, depending on the method used.…”
Section: Introductionmentioning
confidence: 99%